Modification of Silica as a Sealing Rubber Filler with Coupling Agents Hexamethyldisilazane (HDMS) and Methyltriethoxysilane (MTES) - Shely Octavania; Eneng Maryani; Hernawan Hernawan; Lintong Sopandi Hutahaean; Untung Prayudie (Jurnal Keramik dan Gelas Indonesia, 2021)
Materials that can be used in the manufacture of LPG cylinder sealant rubber is silica. However, easily agglomerates so it is not compatible with rubber. Therefore, the silica surface must be modified to reduce agglomeration and improve compatibility with rubber. This study aims to determine the effect of silica modification on the characteristics of LPG cylinder sealing rubber produced. Silica modification is carried out using 2 (two) types of coupling agents, namely HMDS and MTES with and without Si-69. Preparation of rubber compound with SIR 20 raw material is carried out using an open mill tool with a modified silica filler dose of 40 phr. The characteristics of rubber tested were compound maturity test using a Rheometer and tensile strength and elongation at break using a Universal Testing Machine. The test results show that silica modification can accelerate the maturation time of the compound and increase the tensile strength and elongation at break. The maturation time of the rubber compound with silica filler modified by MTES and HMDS was 7 minutes 36 seconds and 7 minutes 53 seconds. The resulting tensile strength and elongation values are 18.8 MPa and 720% (MTES) and 19.0 MPa and 770% (HMDS). The use of MTES and Si-69 as coupling agent for silica produced rubber with tensile strength and elongation at break of 15.9 MPa and 660%.